Developing skills for digital government A review of good practices across OECD governments - Burtscher, Magdalena (OECD Publishing, 2024)
Digital technologies are having a profound impact on economies, labour markets and societies. They also have the potential to transform government, by enabling the implementation of more accessible and effective services. To support a shift towards digital government, investment is needed in developing the skills of civil servants. This paper reviews good practices across OECD countries to foster skills for digital government. It presents different approaches in public administration to organising training activities as well as opportunities for informal learning. It also provides insights into how relevant skills can be identified through competence frameworks, how they can be assessed, and how learning opportunities can be evaluated
Keywords: Employment; Governance; Social Issues/Migration/Health; Science and Technology